Respond to this Question
Similar Questions

math
please check my work. 1. The number of words (x) Tina can type per minute is at Least 50. write and graph and inequality. (I broke it down to these 2 choices because the A & D was incorrect) B. x is less than or equal to 50 C. x 
Solving OneStep Inequalities
Solve this inequality. 2 is greater than or equal to s2 Sorry if I didn't write it in a simple way, I guess. I couldn't write the sign of greater than or equal to. 
Math
please check my work. 1. The number of words (x) Tina can type per minute is at Least 50. write and graph and inequality. (I broke it down to these 2 choices because the A & D was incorrect) B. x is less than or equal to 50 C. x 
trig
solve each equation for 0 less than or equal to x greater than 2ð. cot²xcscx=1 thanks:) step by step please :) 
CALCULUS
Find a formula for the inverse of the function. y=x^2x, x>=(greater than or equal to) 1/2 Please give me a step by step explanation. I think my algebra is wrong... Ty 
proof by mathematical induction
subject is PreCalulus. 2^(k+3) = and < (k+3)! i know how to do proving using mathematical induction when its just an equal sign, but I don't understand what to do when its an inequality. thank you!!! Here is what I would do 
ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE 
Algebra
Hi. I have an answer for this and just need to confirm it. 2x+5(less than or equal to sign here)x + 6. I minused the x's on both sides of the greater then equal to sign; x +5 (greater then or equal to sign) = 6; x +55 (the sign 
mathinequalities
I really don't understand this stuff for example: 9b3b+34<2b10 and 7a+3=24 letters represent variables so they can be anything really. Once you understand this step then the rest of the problem can start to make sense. 
Math
In which step is the error? Step 1: Let x = 1 and y = 1. Step 2: By substitution xy = y^2. Step 3: Multiplying both sides by 1, xy= y^2. Step 4: Adding x^2 to both sides, x^2xy=x^2y^2. Step 5: Factoring, x(xy)=(x+y)(xy).